Health Related Problems and Their Consequences Influencing Old Aged People - Kamlesh K Nigam; Anshuman Sharma (Medsci Publications, 2019)
Introduction- A rapid increase in the number of the elderly as well as their proportion in our population, has led us to being more conscious of the many social, economical, psychological and health problems of the elderly in our country. Of these problems, health and medical problems are generally considered to be important as they affect a large majority of the elderly. It is very important to understand the health needs of the elderly and so solicit their opinion in improving the existing health care system in the country. This article was undertaken study the problems of the elderly with a special focus on the health issues in Bhopal area. Methods- Descriptive study was conducted, sampling was done by purposive sampling method. 190 elderly population participated in the study. Data was collected and properly analyzed by using appropriate statistical tools. Results- Mean age of the elderly population participating in the study was 71.52±8.7 years. Females were 28.4% while males were 71.6%. According to health status minor disease was seen in 52.1% while severe disease in 33.7%. Depression was seen in 10% while heart disease in 23.7%. Conclusion - Elderly population were more prone to stress and health related problems. So special attention is required for their care and support to provide them healthy quality of life.